Effect of adenosine on heart rate variability in humans - Rongen, G A; Brooks, S C; Pollard, M J; Ando, S; Dajani, H R; Notarius, C F; Floras, J S (Clinical science (1979), 1999)
By stimulating afferent nerve endings in skeletal muscle, heart, kidney and the carotid body, adenosine infusion evokes a receptor-specific sympatho-excitatory reflex in humans that overrides its direct negative chronotropic effect. We tested the hypothesis that adenosine increases heart rate by suppressing parasympathetic and augmenting sympathetic components of heart rate variability. High-frequency (PH; 0.15-0.50 Hz) and low-frequency (PL; 0.05-0.15 Hz) components of heart rate variability total power (PT) were determined by spectral analysis. The ratios PH/PT and PL/PH respectively were used to estimate parasympathetic and sympathetic input to the sino-atrial node. Heart rate was recorded before and during a 5 min intravenous infusion of adenosine (140 micrograms.min-1.kg-1) in seven healthy men. Adenosine did not affect blood pressure, but increased heart rate by 33+/-6 beats/min, and reduced PT, PH, PL and PH/PT. In contrast, there was an increase in PL/PH. In a second experiment in nine men, brachial artery infusion of adenosine (15 micrograms.min-1.100 ml-1 forearm tissue) increased heart rate by 3 beats/min, had no effect on PT, PH, PL or PH/PT, yet increased PL/PH. Intra-arterial adenosine exerts a modest effect on heart rate by modulating cardiac sympathetic indices, without affecting parasympathetic indices, of heart rate variability, whereas intravenous infusion of adenosine reduces heart rate variability and raises heart rate by decreasing parasympathetic and increasing cardiac sympathetic tone. These reflex effects may become clinically relevant during adenosine stress testing, or when endogenous adenosine is increased, such as during ischaemia, exercise or vasodepressor reactions, or in heart failure.